Optimasi Waktu Maserasi dan Jenis Pelarut Terhadap Kadar Flavonoid pada Ekstrak Daun Sirsak (Annona Muricata L) - Saraswati, Rosliani; Widyastuti, Fikka Kartika; Kartika Fitri, Ayu Chandra; Kulsum, Umi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Soursop leaf (Annonamuricata L) is a fruit plant originating from the Caribbean, Central America, and South America. In soursop leaves, there are flavonoid compounds, namely phenol compounds with antioxidant, antibacterial, antiviral, anti-inflammatory, anti-allergic, and anticancer activities. The capture of free radicals causes this compound's antioxidant effect via the hydrogen atom donor from the flavonoid hydroxyl group. Some diseases such as atherosclerosis, cancer, diabetes, parkinsonism, Alzheimer's, and decreased immunity have been affected by free radicals in the human body. Flavonoids are of concern because of their medicinal role in the prevention of cancer and cardiovascular disease. One obstacle in the use of soursop leaf extract is the inefficiency of the solvent used so far. This research uses ethanol solvent because ethanol solvent can extract soursop leaves with flavonoid levels 1.36% greater than n-hexane solvents, flavonoid content is 0.66%, and 2propanol solvent is chosen because its polarity is lower than ethanol, so it is expected to extract flavonoid levels. More optimal than ethanol. This study aims to determine the optimization of maceration time and type of solvent on the levels of flavonoids in the soursop leaf extract. This study was designed with a 2 level design factorial method, and two variables changed, namely maceration time (48, 72, 96) hours, ethanol, and 2propanol fractionation solvent types. Fixed variables used were drying time 30 minutes temperature 50oC, sample weight of soursop leaf 10 grams, extraction solvent volume 200 ml, extraction temperature 28oC (room temperature), the method used spectrophotometer. These static and changing variables have a positive effect that can increase phenol levels, and the most influential variables are the type of solvent and extraction time. The best conditions in the cytotoxic extraction process are ethanol solvent and maceration extraction time of 72 hours.